The Effect of Drought on PM Concentrations in the Czech Republic - Adéla Holubová Šmejkalová; Jáchym Brzezina (Aerosol and Air Quality Research)
Abstract The main focus of this study is the effect of drought on air quality in the Czech Republic. PMx (PM10 and PM2.5) concentrations at 21 air quality monitoring stations of different types (rural, suburban and urban) were studied during a 10-year period from 2010 to 2019. Only data measured during the vegetation period (April–September) were used. In addition, other meteorological factors were taken into account as well, in particular wind speed, air and soil temperature and soil moisture. It was found that PM10 concentrations were higher by 26.7 to 46.7% during dry periods with the difference being statistically significant. A strong correlation was found between PM10 and PM2.5 concentrations and the soil temperature and moisture, particularly at the top soil layer (0–10 cm depth). Results of the study show that soil moisture affects the extent of resuspension and soil erosion. Soil moisture values above 36% create unfavourable conditions for resuspension or erosion even when soil temperature is higher than 20°C.